PENGARUH MOTIVASI, KEMAMPUAN DAN KESEMPATAN TERHADAP KINERJA KARYAWAN PADA RUMAH SAKIT UMUM DAERAH NANGA PINOH KABUPATEN MELAWI - Mochammad Faisal Fadli (STIE 'INDONESIA' Pontianak, 2020)
This study aims to determine the effect of motivation, ability and opportunities of employee performance in the general hospital of Nanga Pinoh Melawi District. The number of respondents was 63 respondents. The instrument used for data collection was in the form of a Likert scale questionnaire. This study uses a descriptive method in the form of a survey that is a method that aims to describe the nature of something that is ongoing at the time of the research and examine the causes of a particular symptom Based on data processing using regression analysis, ability variable has a significant positive effect on employee performance. Opportunity variable has a significant positive effect on employee performance. Motivational variables have a positive and significant effect on employee performance at the Nanga Pinoh District General Hospital, Melawi Regency. The coefficient of determination is 0.732. It appears that the ability of the independent variable (Ability, Opportunity and Motivation) in explaining the variance of the variable (Performance) is 73.2% and there are 26.8% variance of the dependent variable that has not been able to be explained by the independent variable in this research model.